POSSIBLE MORTALITY AND NEPHROSIS IN Clarias gariepinus (Burchell, 1822) EXPOSED TO ETHANOL LEAF EXTRACTS OF Senna occidentalis (L.) - ADESANYA, E.O.; IDOWU, A.A; ALEGBELEYE, W.O; ADEKOLA, M.B; TOWOLAWI, A.T; IBRAHIM, F.O. (Nigerian Journal of Fisheries, 2025)
Clarias gariepinus juveniles (250) were stocked; from which 96 fish samples were randomly deployed for range-finding test, while 108 were for the main experiment using 12 plastic tanks of 35 L (4 treatments and 3 replicates), containing 8 fish/tank and 9 fish/tank respectively, filled with 10 L of water. Sub-acute renewal bioassay method was adopted. Range- finding test were done using Senna occidentalis ethanol leaf extracts of 1.00, 1.50, and 2.00 g/ 25 cl of distilled water for 120 hours, followed by the main experiment which had three concentrations of 3.00, 5.00, and 7.00 g/ 25 cl of ethanol leaf extract of S. occidentalis prepared. Daily doses of 5 ml syringes were administered in each treatment for 23 days. The fish were fed twice daily, dead fish in each tank were recorded. The increase in concentrations followed the no-effect observation of the 1.00, 1.50, and 2.00 g/ 25 cl used for the range-finding test. Analysis of variance were used to assess the data. The mortality rate significantly (p < 0.05) varied across the main experiment's treatments and increased with increased concentrations. Treatment A (control) showed no visible lesion, treatment B (3.00 g/ 25 cl) showed vacuolation of the epithelial lining's cytoplasm, treatment C (5.00 g/ 25 cl) showed moderate tubular epithelial necrosis, and treatment D (7.00 g/ 25 cl) showed both glomerular and tubular epithelial necrosis. The toxicity tolerance of C. gariepinus showed that the degree of damage observed increased with an increase in the concentration of S. occidentalis.